Factors Related to the Quality of Life of Patients with Breast Cancer Undergoing Chemotherapy at Dharmais Cancer Hospital - Mutiara, Septy; Yulianto, Sherly Putri; Shinta, Shinta; Marta, Shinta; Susilowati, Shinta; Masfufah, Dian Siti; Idu, Cicirosnita Jayadi; Ngasu, Kristina Everentia (Indonesian Journal of Cancer, 2025)
Background: Breast cancer is one of the most common cancers in the world, and patients commonly undergo chemotherapy. Chemotherapy adherence and other factors are associated with reduced quality of life (QoL) in patients with breast cancer. This study aimed to determine factors that influence the decreased QoL of breast cancer patients and the probability of reducing the QoL of patients with breast cancer.Method: A cross-sectional research design was employed with 159 respondents, using a purposive sampling technique. The criteria were patients with breast cancer undergoing chemotherapy, without experiencing decreased activity due to disability or respiratory disorders. The questionnaires were the Adolescent Scale Activity Questionnaire (ASAQ), chemotherapy compliance questionnaire, International Physical Activity Questionnaire (IPAQ), body image scale questionnaire, Malnutrition Screening Tool (MST), spiritual well-being scale (SWBS), and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Breast 23 (EORTC QLQ-BR23). Analysis was conducted using a chi-square test and a multivariate logistic regression. The research has been tested ethically by Dharmais Cancer Hospital.Results: Most patients with breast cancer undergoing chemotherapy at Dharmais Cancer Hospital were in the age category of ≤ 45 years (38.5%), secondary education or less (76.1%), unemployed (64.8%), and stage III (56.6%). The overall research results were sedentary behavior (OR=0.05, 95%CI:0.01-0.38), chemotherapy adherence (OR=9.94, 95%CI:2.12-46.57), daily physical activity (OR=5.65, 95%CI:1.21-26.40), body image (OR=20.44, 95%CI:2.59-161.61), and spiritual well-being (OR=10.78, 95%CI:2.86-40.57), identified as factors associated with QoL in patients with breast cancer. Meanwhile, the strength of the most significant relationship was high sedentary behavior (OR=9.10, SE: 1.16), and the smallest was low spiritual well-being (OR=0.07, SE: 1.03).Conclusion: We found that high sedentary behavior, non-compliant chemotherapy adherence, low daily physical activity, negative body image, and low spiritual well-being were related to decreased QoL in patients with breast cancer.